Development and experiences of an internet-based acceptance and commitment training (I-ACT) intervention in ice hockey players: a qualitative feasibility study - Reinebo, Gustaf; Björverud, Linda G.; Parling, Thomas; Andersson, Gerhard; Jansson-Fröjmark, Markus; Lundgren, Tobias (Frontiers in Sports and Active Living, 2024)
Internet-based psychological interventions have increased the accessibility of evidence-based treatments in clinical psychology but are still an unexplored delivery format in sport psychology research. This study describes the development and evaluates the experiences of an internet-based acceptance and commitment therapy/training (I-ACT) intervention in ice hockey players focusing on performance enhancement and a sustainable sport participation. I-ACT consisted of seven weekly modules and the feasibility of the intervention was investigated using a qualitative research design. Four national level ice hockey players took part of I-ACT and were interviewed about their experiences using a semi-structured protocol.Interview transcripts were analyzed using qualitative content analysis. Findings suggest that the content of I-ACT was comprehensible, relevant, and that it was possible to put the psychological skills into practice. I-ACT was described as helpful to the ice hockey players either in their sport performance or in their life outside of sport. The internet-format was generally perceived as positive, flexible, and a feasible option for delivering psychological interventions in an elite sport context. Some concerns were raised regarding the timing of the intervention at the end of the season, and some players also wished for more time to complete I-ACT. It was also expressed that some of the exercises could have been better adapted for goaltenders. Further trials are needed to evaluate the effects of I-ACT on performance and mental health outcomes in various sport populations using robust quantitative research methodology. Internet-based psychological interventions are a potential future opportunity to make evidence-based practices more accessible for athletes.